1990
DOI: 10.1002/smr.4360020103
|View full text |Cite
|
Sign up to set email alerts
|

A model for assembly program maintenance

Abstract: This paper presents a model for understanding assembly programs for software maintenance. It is based on the theory that explicit representation of various structural and functional elements of code and multiple relationships among them will aid program Understanding and thus software maintenance. We present a parsing technique to extract all the required elements from assembly code to populate the model. The model is a reverse engineering technique. We use the term reverse engineering in its broad sense to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…To expedite the software maintenance process, the business rule extraction process should be automated as much as possible. However, our previous work on software reverse engineering (Heisler, Tsai and Powell, 1989;Chen et al, 1990;Chen, Tsai and Chen, 1992;Heisler, Kasho and Tsai, 1993;Ong and Tsai, 1993;Chen et al, 1994;Joiner et al, 1994, Huang, Tsai andSubramanian, 1996;Joiner and Tsai, 1997) has shown that it is extremely difficult, if not impossible, to devise an automatic program understanding tool. This is also true for business rule extraction.…”
Section: Business Rule Extraction Criteriamentioning
confidence: 99%
“…To expedite the software maintenance process, the business rule extraction process should be automated as much as possible. However, our previous work on software reverse engineering (Heisler, Tsai and Powell, 1989;Chen et al, 1990;Chen, Tsai and Chen, 1992;Heisler, Kasho and Tsai, 1993;Ong and Tsai, 1993;Chen et al, 1994;Joiner et al, 1994, Huang, Tsai andSubramanian, 1996;Joiner and Tsai, 1997) has shown that it is extremely difficult, if not impossible, to devise an automatic program understanding tool. This is also true for business rule extraction.…”
Section: Business Rule Extraction Criteriamentioning
confidence: 99%
“…To understand software, a functionality model is needed. This functionality model must be tightly coupled with the code (S. Chen et al, 1990Chen et al, , 1992Heisler, 1993;Huang et al, 1995) as the user's main aim is to understand the code. There should be traceability between the functionality model and the code.…”
Section: Research Topicsmentioning
confidence: 99%
“…Most proposed systems to support software understanding are built around the concept of a program information base (Ambras and O'Day, 1988;Calliss et al, 1988;Chen, Y.F. et al, 1990;Chen, S . et al, 1990;Collofello and Orn, 1988;Heisler et al, 1993;Linton, 1984;Rajlich et al, 1988;Yau and Tsai, 1987).…”
Section: Related Workmentioning
confidence: 99%